Cross Cultural Communication Strategies for Teaching Teams in PKBM Junggel Salatiga, Indonesia - Vieira, Driellen; Ismanto, Bambang; Iriani, Ade (Universitas Pendidikan Mandalika, 2025)
This study aims to examine cross-cultural communication in the multicultural environment of PKBM Junggel School Salatiga. The research employs a descriptive qualitative method, utilizing observation and in-depth interview techniques. Participants were selected through purposive sampling, comprising 13 teachers and 2 principals with over a year of experience working in multicultural teams. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that cross-cultural communication at PKBM Junggel School Salatiga runs effectively despite various challenges. The diverse backgrounds of educators, both local and international, make Junggel School a rich learning space with perspectives that are prone to miscommunication. Key challenges include differences in communication styles (high vs. low context), culture shock, and interpretation of non-verbal cues such as facial expressions, eye contact, and body language. The effectiveness of cross-cultural communication is achieved through specific managerial strategies, including cultural training, reflective forums, and open communication. These strategies have successfully created an inclusive, harmonious, and responsive collaborative environment that meets the needs of global learners. Diversity is viewed not as an obstacle but as a strategic asset that enriches the pedagogical approach and builds education based on values of tolerance and mutual respect.